2023
DOI: 10.3390/ijms24076393
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Mechanisms of a Polyphenolic Combination of Kaempferol and Fisetin in Triple-Negative Breast Cancer Cells

Abstract: Herein, we investigate the combinatorial therapeutic effects of naturally occurring flavonoids kaempferol (K) and fisetin (F) on triple-negative breast cancer (TNBC: MDA-MB-231 cell line). Dose-dependent MTT assay results show that K and F exhibited cytotoxicity in MDA-MB-231 cells at 62 and 75 μM (IC50), respectively, after 24 h. However, combined K + F led to 40% and more than 50% TNBC cell death observed at 10 and 20 μM, respectively, which revealed the synergistic association of both. The combination of K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Apoptosis-inducing properties in transformed cells are key features of a potential chemopreventive agent [ 36 ]. Numerous reports have shown that fisetin and kaempferol induce cytotoxic effects on human cell lines by arresting the cell cycle and apoptosis, such as: bladder cancer [ 36 ], intestinal cancer [ 27 , 37 ], breast cancer [ 38 , 39 ], gastric cancer [ 40 , 41 ], prostate cancer [ 42 ], pancreatic cancer [ 43 ], ovarian cancer [ 44 ], liver cancer [ 45 ], skin cancer [ 46 ], cervical cancer [ 36 ], lung cancer [ 47 ], brain cancer [ 48 ], osteosarcoma [ 49 ], melanoma [ 50 ], multiple myeloma [ 51 ], leukemia [ 18 , 52 ], endometrial cancer [ 53 ], and head and neck cancers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis-inducing properties in transformed cells are key features of a potential chemopreventive agent [ 36 ]. Numerous reports have shown that fisetin and kaempferol induce cytotoxic effects on human cell lines by arresting the cell cycle and apoptosis, such as: bladder cancer [ 36 ], intestinal cancer [ 27 , 37 ], breast cancer [ 38 , 39 ], gastric cancer [ 40 , 41 ], prostate cancer [ 42 ], pancreatic cancer [ 43 ], ovarian cancer [ 44 ], liver cancer [ 45 ], skin cancer [ 46 ], cervical cancer [ 36 ], lung cancer [ 47 ], brain cancer [ 48 ], osteosarcoma [ 49 ], melanoma [ 50 ], multiple myeloma [ 51 ], leukemia [ 18 , 52 ], endometrial cancer [ 53 ], and head and neck cancers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ackland et al (2005) discovered that quercetin and kaempferol synergistically reduce cell proliferation in the PMC42 human mammary cell line at physiological concentrations between 1 and 10 of 5 ÌM. Afzal et al (2023) reported that the combination of kaempferol and laccasein is more effective in inhibiting the proliferation of TNBC cancer cells (MDA-MB-231) than either substance alone. The co-administration of kaempferol and laccasein resulted in the downregulation of p-Akt protein expression and inhibition of the PI3K/Akt pathway.…”
Section: Mechanisms Of Kaempferol Against Gynaecological Malignanciesmentioning
confidence: 99%
“…Kaempferol in low concentration was very effective when combined with curcumin at 12.5 μM (IC50). This combination of kaempferol and curcumin showed significant antiproliferative activity against colon cancer cells (HCT‐15) and human normal lymphocytes [ 46 , 47 ]. Recent studies in the literature clarified that kaempferol is a promising phytopharmaceutical used in the management of colon cancer via mediating inflammation and signal transduction pathways [ 48 ].…”
Section: Kaempferolmentioning
confidence: 99%